Pengaruh Kualitas Produk, Harga dan Kualitas Pelayanan terhadap Kepuasan Konsumen (Studi pada Warung Lindekss Kota Jambi) - Yuwita Rapita Sari; Agustina Mutia; Rabiyatul Alawiyah (ARZUSIN, 2026)
The rapid development of the culinary industry and the increasing share of household expenditure on food consumption have intensified competition among business actors, making customer satisfaction a key factor in ensuring business sustainability. However, studies that specifically examine the influence of product quality, price, and service quality on customer satisfaction in local micro-scale culinary enterprises remain relatively limited, particularly in the context of Warung Lindekss in Jambi City. This study aimed to analyze the effect of product quality, price, and service quality on customer satisfaction at Warung Lindekss Jambi City. A quantitative approach with a survey design was employed, involving 96 respondents selected using a simple random sampling technique. Data were collected through a structured questionnaire and analyzed using multiple linear regression with the aid of EViews software. The results showed that product quality and service quality had a positive and significant effect on customer satisfaction, whereas price did not have a significant effect. Simultaneously, product quality, price, and service quality had a significant effect on customer satisfaction. These findings reinforce the concept of customer satisfaction in marketing theory, which emphasizes product and service quality as the main determinants of satisfaction, while also providing practical implications for micro-scale culinary business owners to optimize product and service quality in order to enhance customer satisfaction and loyalty, as well as opening avenues for further research through an expanded scope and the inclusion of additional variables related to customer satisfaction.